Biowaste valorization by conversion to nanokeratin-urea composite fertilizers for sustainable and controllable nutrient release. (October 2021) - Sree, G. Vanthana; Rajasekaran, P.; Bazaka, Olha; Levchenko, Igor; Bazaka, Kateryna; Mandhakini, Mohandas
Abstract: Novel nanocomposite-based fertilizers produced through intelligent disposal of an abundant carbon-reach biological waste product, i.e. poultry feathers, will play an increasingly important role in sustaining global economy. Affordable, efficient, and sustainable, these fertilizer platforms derived from low or even negative value products provide a competitive alternative to conventional chemical agents. In this work, bio-fertilizer nanocomposites are fabricated from urea and keratin derived from feathers, the primary negative value by-products of poultry industry, and loaded into sustainable matrix, i.e. wood chips for sustained nutrient release. Urea-coated nanokeratin composites retain a significant fraction of the extracted organic and inorganic nutrients, and application of the loaded wood chips on the soil led to a significant improvement in germination rate, height of plant and number of leaves of cowpea compared to using urea alone, attributed to sustained release of nitrogen from the composite that prevented over-fertilization. Presence of disulphide bonds in the nanocomposite enables more efficient degradation of nanokeratin by soil microbes, providing a steady supply of essential nutrients like carbon, sulphur and nitrogen to plants. Our findings described in this communication suggest that nanokeratin-loaded wood chips may provide an efficient environmentally friendly strategy for improving soil fertility without the release of nitrous oxide, an anthropogenic greenhouse gas known to trap 300 times more heat than CO2 .